Widespread sensors and Artificial Intelligence for a novel Safety Management System at the Seveso sites. - Silvia M. Ansaldi; Paolo Bragatto (Chemical Engineering Transactions, 2022)
Sensors may be pervasively distributed throughout the plant, in the workplace and also worn by workers. They offer, coupled with Artificial Intelligence, a great opportunity to make safety management at Seveso sites much more dynamic and participatory. The article discusses how it is possible to exploit innovative systems based on pervasive sensors and AI to introduce important elements of flexibility and resilience in the SMS-MAH, while maintaining the consolidated structure envisaged by the Seveso legislation.